The competitive advantage of nations : with a new introduction - Porter, Michael E., 1947- (New York : Free Press, 1998)
Foundations. Industries. Nations. Implications.
Keywords: Competition; Industrial policy; International business enterprises; Economic development; Industrial management; Strategic planning; Competition, International; Industrial policy; International business enterprises